2011
DOI: 10.1016/j.chemosphere.2011.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new ozonation disinfection byproducts of 17β-estradiol and estrone in water

Abstract: Estrogens are a class of micro-pollutants found in water at low concentrations (in the ng L(-1) range), but often sufficient to exert estrogenic effects due to their high estrogenic potency. Disinfection of waters containing estrogens through oxidative processes has been shown to lead to the formation of disinfection byproducts, which may also be estrogenic. The present work investigates the formation of disinfection byproducts of 17β-estradiol (E2) and estrone (E1) in the treatment of water with ozone. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 40 publications
(46 reference statements)
3
14
0
4
Order By: Relevance
“…In order to decrease risks of E2 toxicity in water and wastewater, the degradation of this molecule until its removal were investigated by several authors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Except that according to literature, no study has shown the degradation of the 17β-estradiol using Electro-Fenton process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to decrease risks of E2 toxicity in water and wastewater, the degradation of this molecule until its removal were investigated by several authors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Except that according to literature, no study has shown the degradation of the 17β-estradiol using Electro-Fenton process.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, based on (AOPs) such as: photocatalytic degradation [1][2][3][4][5], ozonation [6,7], H 2 O 2 photolysis (UV/H 2 O 2 ) [8], photo-Fenton (H 2 O 2 /Fe 2+ /UV) [9][10][11][12], have investigated and showed the degradation of endocrine disrupting chemicals (EDCs).…”
Section: Introductionmentioning
confidence: 99%
“…Applying UPLC-MS/MS with QqQ-and QTOF-detectors, two ozonation products of each of the two estrogens 17β-estradiol and estrone were detected. One could be characterized as 10-ε-17β-dihydroxy-1,4-estradieno-3-one, and three others were tentatively identified (Pereira et al 2011). These oxidation by-products were found to be persistent even after application of high ozone dosages.…”
Section: Transformation Productsmentioning
confidence: 95%
“…The authors also used spectral libraries to identify potential matches. Radjenović, et al [13], de Oliveira Pereira, et al [14] and Larcher, et al [15] employed LC coupled to a hybrid high-resolution mass spectrometer to separate, identify and assign structures to OTPs. Benner and Ternes [16] based the structural elucidation of the OTPs of propranolol on product ion fragmentation trees generated by LC coupled to multi-stage tandem mass spectrometry (MS n ).…”
Section: Introductionmentioning
confidence: 99%
“…E1 has been observed to be almost completely removed during wastewater disinfection using ozone [24]. However, bench-scale studies investigating the fate and transformation of E1 during ozonation have revealed the formation of OTPs [11,14]. …”
Section: Introductionmentioning
confidence: 99%